Determinants of legitimacy of Islamic bonds (Sukuk) in Malaysia: Shariah supervisory board as a moderator - Ahmed, Essia Ries (School of Business Innovation & Technopreneurship, 2017)
The Islamic financial institutions in Malaysia have been chosen primarily because these Islamic institutions play a significant role in the development of the Islamic finance industry in the country in general (Sulaiman, Majid, & Ariffin, 2011). The present study focuses on some of the Sukuk selected determinants, which are pricing, type of 18 structure, Shariah auditing, Shariah Supervisory Board (SSB), Shariah Risk and Shariah-related documentation. In order to determine the factors which are important elements for the legitimacy of Sukuk these factors or determinants ought to be taken into consideration in order to improve the legitimacy of the Sukuk and make it compatible with Shariah principles.